Effects of Magnoline on P-Selectin's Expression in Diabetic Rats and its Reno-Protection - Yang Zhou; Feng Wang; Lirong Hao; Niansong Wang (Karger Publishers, 2013)
Background and Objective: Magnoline is an active ingredient of magnolia fargesii with anti-inflammatory and anti-platelet effects. The objective is to explore the renoprotection of magnoline in diabetic rats and its effects on P-selectin. Methods: Thirty-six rats were randomized into 4 groups-normal control group (C), diabetic group (D), small-dose magnoline treatment group (M1) and large-dose magnoline treatment group (M2) (n=9 in each group). Streptozotocin was selected to construct diabetic rat model, and group M1 and group M2 were treated with magnoline 0.5mg/Kg.d and 2mg/Kg.d respectively. Urinary albumin excretion rate, renal function, levels of P-selectin and TGF-β1 were observed after 16 weeks. Results: Levels of albuminuria and serum creatinine of group M1 (1078.9 ± 77.3μg/24h, 29.7 ± 3.9μmol/L) and M2 (852.9 ± 80.1μg/24h, 30.9 ± 2.9μmol/L) were lower than group D (1572.8 ± 176.2μg/24h, 39.4 ± 4.1μmol/L) (P Conclusions: Magnoline has reno-protective effects on diabetic rats which may be related to the inhibition of P-selectin.